2015
DOI: 10.1007/s00217-015-2515-x
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of distinctive volatiles, descriptive sensory analysis and consumer preference of differently ripened and post-harvest handled pineapple (Ananas comosus [L.] Merr.) fruits

Abstract: Volatiles of differently ripened fresh pineapples were investigated by a non-targeted profiling analysis comparing fruits harvested at full maturity exported by rapid air freight to pineapples harvested at an earlier green-ripe stage. The latter fruits were exported by sea freight and analysed upon arrival at their destination and after post-harvest flavour genesis. Volatiles were analysed by headspace solid-phase microextraction, gas chromatography–mass spectrometry and multivariate statistical data analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Furthermore, 16 terpenes, nine alcohols, six γ-and δ-lactones, five aldehydes, four undecaene hydrocarbons, and two furanones were tentatively identified. This qualitative composition of volatiles resembled that previously reported for fresh 'MD2' pineapples [4,5,19] and juice obtained thereof [20], except for some juicespecific constituents, such as free fatty acids and diverse norterpenoids, that were not found in the fresh-cut samples assessed herein.…”
Section: Assignment Of Fresh-cut Pineapple Volatilessupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, 16 terpenes, nine alcohols, six γ-and δ-lactones, five aldehydes, four undecaene hydrocarbons, and two furanones were tentatively identified. This qualitative composition of volatiles resembled that previously reported for fresh 'MD2' pineapples [4,5,19] and juice obtained thereof [20], except for some juicespecific constituents, such as free fatty acids and diverse norterpenoids, that were not found in the fresh-cut samples assessed herein.…”
Section: Assignment Of Fresh-cut Pineapple Volatilessupporting
confidence: 89%
“…In a previous study, fully ripe air-freighted pineapples and three post-harvest stages of green-ripe, sea-freighted fruit were assessed by solidphase microextraction and gas chromatography-mass spectrometry (HS-SPME-GC-MS), revealing clear-cut differences in their volatiles [4]. In addition, the odour, taste, and overall preference of air-freighted pineapples were significantly better rated by a consumer panel compared to sea-freighted fruit assessed at two post-harvest stages [5]. By analogy to fresh fruit, also quality of freshcut products obtained from fully ripe and green-ripe seafreighted pineapples may differ.…”
Section: Introductionmentioning
confidence: 99%
“…The fresh juice group had the highest amount of volatile compounds, and the areas corresponded with twelve esters, three acids, three alcohols, three ketones, three aldehydes, and two unknown compounds. Several authors reported that esters are the major volatile compounds in pineapple and may contribute to the pronounced fruity aroma, although their qualitative and quantitative composition may differ among the analyzed samples .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies about fruit ripening metabolomics mostly focused on climacteric fruits, such as banana, mango, capsicum, dates, avocado, peach, climacteric melon, and mangosteen [9][10][11][12][13][14][15][16]. On the other hand, only a few of non-climacteric ripening processed fruit had been elucidated using metabolomics approach, such as cherry, blackcurrant, blueberry, non-climacteric melon, and pineapple [15,[17][18][19][20][21]. Previous metabolomics studies on non-climacteric fruit employed mass spectrometry-based instruments, such as gas chromatography-mass spectrometer (GC-MS) or liquid chromatography-mass spectrometer (LC-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Previous metabolomics studies on non-climacteric fruit employed mass spectrometry-based instruments, such as gas chromatography-mass spectrometer (GC-MS) or liquid chromatography-mass spectrometer (LC-MS). Several studies performed a combination of headspace-solid phase microextraction (HS-SPME) with GC-MS to measure volatile compounds during the ripening process [15,20]. Reports on pineapple ripening have been focused in volatile and phenolic compounds using HS-SPME-GC-MS, high-performance liquid chromatography with diode array detection and electrospray ionization multiple-stage mass-spectrometry (HPLC-DAD-ESI-MS n ), and electrospray ionization mass spectrometry (ESI(-)FT-ICR MS) [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%